Self-determined motivation and life satisfaction in portuguese veterans athletes - Batista, Marco (2018)
The aims of this work were to determine correlations and predictive variables, between the levels of motivation, basic psychological needs and life satisfaction of Portuguese veteran athletes. The sample consisted in 684 Portuguese veteran athletes of both genders, aged between 30 and 90 years (M = 43.78 DP = 8.61), competitors of various modalities. As instruments we used the Behavioral Regulation in Sport Questionnaire (BRSQ), the Basic Psychological Needs Scale Exercise (BPNES), the Satisfaction with Life Scale (SWLS) and Positives and Negatives Affections Scale (PANAS). It was applied the bivariate Pearson correlation test and multiple linear regression. The results showed that the veteran athletes present a good selfdetermination for the sport practice, being their welfare levels in life satisfaction related to the same self-determination, but rather dependent on the affections produced by sports. This study is presented as a contribution to understanding the role of sport in promoting wellness in veteran sports population.